Stability Differences among Okra Genotypes for Seed Quality - J.S. KANWAR,; SALESH KUMAR JINDAL,; SATISH KUMAR, (Seed Research, 2026)
Performance of 16 okra genotypes in respect of seed quality related traits were evaluated under three environments for stability analysis. GxE interactions were significant for number of seeds per pod, seed weight per pod, seed yield per hectare, seed germination and seed vigour index. Linear component as well as non-linear component equally contributed GxE interactions in number of seeds per pod, seed weight per pod, seed yield per hectare and seed germination. Linear component was significant against non-linear component in seed vigour index only. Punjab-8 and Punjab Padmini were stable for all the characters, however, all the genotypes were stable for seed yield per plant and seed vigour index.